STUDI DOKUMENTASI PADA KASUS PASIEN YANG MENINGGAL DENGAN COVID-19 DI RUANG INTENSIVE RUMAH SAKIT X [DOCUMENT ANALYSIS OF THE CASES OF PATIENTS WHO DIED FROM COVID-19 IN THE INTENSIVE CARE UNIT OF HOSPITAL X] - Meliza Yuliana; Siti Nurbaity; Alice Pangemanan; Anthina Luturmas (Nursing Current: Jurnal Keperawatan, 2023)
Coronavirus-2019 is an infectious disease caused by SARS-CoV-2 and has been a pandemic for four years. Various patient characteristics are risk factors for the severity of the condition and increased mortality in patients with COVID-19. Research objectives: This study aims to describe the cases of patients who died from COVID-19 in the intensive care unit at Hospital X in Tangerang. A retrospective, quantitative descriptive design with a document analysis was carried out in this study. 81 medical records were selected using the purposive sampling method and analysed from January to October 2021. This study showed that an age >65 years was the most common age for a total of 32 (39.5%) patients. Furthermore, most of the respondents were male patients for a total of 51 (63%). There were 54 (66.7%) patients with severe symptoms, and 76 (93.8%) patients using ventilators. Hypertension and diabetes were the most common comorbidities, found among 14 (17.3%) patients. The results of respiratory acidosis was the most common condition in 33 (40.7%) patients. In addition, 58 (71.6%) patients detected pneumonia on chest CT scan. 75 (92.5%) patients had a D-dimer >1.0, 53 (63.4%) patients had a CRP >200, and 54 (66.7%) patients had a PCT <0.5. Conclusion: It is necessary to conduct research on the relationship between the characteristics of patients who died with COVID-19. BAHASA INDONESIA ABSTRAK Coronavirus-2019 adalah penyakit menular yang disebabkan oleh SARS-CoV-2 dan menjadi pandemic selama empat tahun. Berbagai karakteristik pasien menjadi faktor risiko keparahan kondisi dan peningkatan angka mortalitas pada pasien dengan COVID-19. Penelitian ini bertujuan untuk mengetahui gambaran kasus pasien yang meninggal dengan COVID-19 di ruang intensif rumah sakit X di Tangerang. Desain retrospektif deskriptif kuantitatif dengan studi dokumentasi dilakukan dalam penelitian ini. 81 rekam medis dipilih dengan metode purposive sampling dan dianalisis pada bulan Januari – Oktober 2021. Penelitian ini menunjukkan bahwa usia >65 tahun adalah usia terbanyak, yaitu sebanyak 32 (39.5%) pasien, dengan dominasi pasien laki-laki sebanyak 51 (63%) orang, dengan gejala berat sebanyak 54 (66.7%) pasien, serta sebanyak 76 (93.8%)  pasien menggunakan ventilator. Hipertensi dan diabetes merupakan komorbid terbanyak, yaitu 14 (17.3%) pasien, dengan hasil asidosis respiratorik sebagai kondisi terbanyak, yaitu 33 (40.7%) pasien, gambaran pneumonia sebanyak 58 (71.6%) pasien pada pemeriksaan CT-scan thorax, 75 (92.5%) pasien dengan nilai D-dimer >1.0, 53 (63.4%) pasien dengan nilai CRP >200, dan sebanyak 54 (66.7%) pasien dengan nilai PCT <0.5. Saran untuk penelitian selanjutnya, perlu dilakukan penelitian terkait hubungan antar karakteristik pasien yang meninggal dengan COVID-19.